Efektivitas Ozonated VCO Terhadap Penyembuhan Luka Full Thickness Skin Graft Ditinjau dari Proliferasi Endotel Progenitor Cell dan Angiogenesis pada Tikus Sprague Dawley - Sidauruk, Rollin Hansen; Yuniati, Renni; Handojo, Djoko (RSUP Dr. Kariadi, 2021)
Abstract Background : Full thickness Skin graft is one technique to accelerate wound healing. EPC proliferation and new blood vessel formation have an important role in the success of Ful thickness Skin graft. Ozone content in Ozonated VCO has the ability to increase growth factors so that it can accelerate wound healing Aims : This study was aimed to prove the effects of ozonated vco in various doses in increasing EPC proliferation and angiogenesis in full thickness skin graft wounds. Methods : This research is an experimental study with randomized post test only with parallel group design. 40 Sprague Dawley rats performed autologous Skin grafts at the same time. Samples were randomly divided into 8 groups, two control groups (X1 and X5), and 6 other groups were given a multi-dose ozonated oil 50.6 mg / ml (X2, X6), 101.3 mg / ml (X3, X7) , 202.6 mg / ml (X4, X8). Conduct termination on day 6 and day 12. Examination of the number of EPC proliferation and the number of angiogenesis in each group. Data were analyzed by Saphiro Wijk, ANOVA, post hoc benferonni and pearsons Results : The number of EPC proliferation in groups X1, X2, X3, X4, X5, X6, X7, X8 has a mean of 6.2 + 0.837, 10 + 1.581, 13.80 + 2.049, 14.80+ 2,280, 9.40 + 2,074 , 13.20 + 1,483, 19,0 + 2,055 and 19.20 + 1,095.The number of Angiogenesis in groups X5, X6, X7, X8 has a mean of 9.20 + 1,095,14,60 + 2,881,17,40+ 3,286, 18,80 + 2,168,17,40 + 3,286,18.80+ 2,168. The administration of ozonated VCO dose of 202.6 mg / ml gave the best results in the amount of angiogenesis (p = 0.001) and the amount of angiogenesis (p=0,001).Correlation analysis between EPC proliferation and angiogenesis showed a significant correlation (p = 0.001 and r = 0.738). Conclusion : Ozonated oil can increase the number of EPC proliferation and angiogenesis in the wound healng process of Full thickness Skin graft. The ozone dose of 202,6 mg / ml showed the best effect on increase wound healing process. Keyword : Full thickness skin graft, Ozonated oil , EPC, Angiogenesis